Advanced MRI techniques: biomarkers in neuropsychiatric lupus. (April 2017) - Sarbu, N; Toledano, P; Calvo, A; Roura, E; Sarbu, M I; Espinosa, G; Lladó, X; Cervera, R; Bargalló, N
Objectives: The objective of this study was to determine whether advanced MRI could provide biomarkers for diagnosis and prognosis in neuropsychiatric systemic lupus erythematosus (NPSLE). Methods: Our prospective study included 28 systemic lupus erythematosus (SLE) patients with primary central NPSLE, 22 patients without NPSLE and 20 healthy controls. We used visual scales to evaluate atrophy and white matter hyperintensities, voxel-based morphometry and Freesurfer to measure brain volume, plus diffusion-tensor imaging (DTI) to assess white matter (WM) and gray matter (GM) damage. We compared the groups and correlated MRI abnormalities with clinical data. Results: NPSLE patients had less GM and WM than controls ( p  = 0.042) in the fronto-temporal regions and corpus callosum. They also had increased diffusivities in the temporal lobe WM ( p  < 0.010) and reduced fractional anisotropy in the right frontal lobe WM ( p  = 0.018). High clinical scores, longstanding disease, and low serum C3 were associated with atrophy, lower fractional anisotropy and higher diffusivity in the fronto-temporal lobes. Antimalarial treatment correlated negatively with atrophy in the frontal cortex and thalamus; it was also associated with lower diffusivity in the fronto-temporal WM clusters. Conclusions: Atrophy and microstructural damage in fronto-temporal WM and GM in NPSLE correlate with severity, activity and the time from disease onset. Antimalarial treatment seems to give some brain-protective effects.